Contributing forces in achieving foreseeable Industrial and Services Sector Growth Rates and their impact on GDP in the Sultanate of Oman - Veerasamy , Rengarajan; Younas , Afshan; Hussainy , Syed Sadullah; Al-Wahaibi , Mahmood (Journal of Ecohumanism, 2024)
The Sultanate of Oman has reported around 4.31% of economic growth rate in the year 2022 over the previous year 2021. It is evident that the country has been able to achieve good economic growth and prosperity. The industrial policies of the country have been relevant and highly motivating for both national and international investors, so the economy is now able to attract both local and international investors to invest in both manufacturing and services sector. The Sultanate of Oman is diversifying its oil dependency to non-oil dependency sector, thus, the pressure on generating adequate revenue from oil exports can be reduced. The economy is diversifying its economic resources towards achieving sustainable industrial and services sector growth. The country had been able to achieve a growth rate of 3.09% in the year 2021. The increase in economic growth rate is fully assisted by growing rates in household consumption (16.8%) and raising retaining capital investments (more than 20 billion in US, dollars, keeping the inflation rates in the range of 1.5 – 2.8%. In addition to these factors, there must be other contributing forces like growth in industrial productivity, services sector contribution for the GDP, contribution of manpower, government spending, spending on health and education etc. The economy is current in the path of achieving 2040 vision in terms of economic development. Thus, understanding the contributing forces to enhance the manufacturing value added and service sector value added is important for the economy. Thus, research must be carried out essentially to find the relationship between GDP and the contributing factors such as industrial production and services sector contribution and other related variables. An initial analysis reveals that GDP in (US ) is correlated with manufacturing value added with 1.00 positively and with services sector contribution with 0.635 positively. It is found that the country has got the greater potential in achieving maximum in manufacturing value added and in service sector value added. which can be converted into their competitive edge through policies and procedures